Adolescent mental health problems in early stages of the COVID-19 pandemic were masked by lockdown measures and restrictions - Rockstroh, Franziska; Kaess, Michael (BJPsych Open, 2022)
In the BJPsych Open Wong et al examined the influence of lockdown stringency during early stages of the COVID-19 pandemic on psychiatric emergency presentations among children and adolescents from ten countries. Data from March and April 2019 were compared with the same time frame in 2020, with particular focus on self-harm admissions. In this editorial, the publication is summarised and potential implications for the field and future studies are discussed.
Gesehen am 25.01.2023